An Analysis of the Drivers of Microfinance Rating Assessments - Leif Atle Beisland; Roy Mersland (Nonprofit and Voluntary Sector Quarterly, 2012)
Rating assessments of microfinance institutions (MFIs) are claimed to measure a combination of creditworthiness, trustworthiness, and excellence in microfinance. Using a global data set covering reports from 304 microfinance institutions, this study suggests that these ratings are mainly driven by size, profitability, and risk. The overall results suggest that microfinance ratings convey information similar to that communicated by traditional credit ratings. All results are remarkably consistent across rating agencies. The determinants of the rating grades are found to be the same in all subsamples.
Keywords: 650